The Customary of the Shrine of St. Thomas Becket at Canterbury Cathedral : Latin Text and Translation (Foundations (ARC Humanities Press), 2022)
The shrine of St Thomas Becket at Canterbury Cathedral was one of the most popular pilgrim destinations in medieval Europe, as well as the focal point for the liturgy of the cathedral's monastic community. In 1428 the keepers of the shrine composed a customary detailing its day-to-day operation, including the opening hours, decoration, maintenance, and staffing. This unique survival offers a rare glimpse into the realities of organizing a pilgrimage site in a major medieval church, and the Latin text with facing English translation is provided for the first time. A comprehensive introduction and extensive notes set the Customary within the context of the cathedral, its liturgy, and pilgrim practice more widely.